Brain-targeting autoantibodies in patients with dementia - Staabs, Finja; Foverskov Rasmussen, Helle; Buthut, Maria; Höltje, Markus; Li, Lucie Y.; Stöcker, Winfried; Teegen, Bianca; Prüss, Harald (Frontiers in Neurology, 2024)
Autoantibodies against proteins in the brain are increasingly considered as a potential cause of cognitive decline, not only in subacute autoimmune encephalopathies but also in slowly progressing impairment of memory in patients with classical neurodegenerative dementias. In this retrospective cohort study of 161 well-characterized patients with different forms of dementia and 34 controls, we determined the prevalence of immunoglobulin (Ig) G and IgA autoantibodies to brain proteins using unbiased immunofluorescence staining of unfixed murine brain sections. Autoantibodies were detected in 21.1% of dementia patients and in 2.9% of gender-matched controls, with higher frequencies in vascular dementia (42%), Alzheimer's disease (30%), dementia of unknown cause (25%) and subjective cognitive impairment (16.7%). Underlying antigens involved glial fibrillary acidic protein (GFAP), glycine receptor and Rho GTPase activating protein 26 (ARHGAP26), but also a range of yet undetermined epitopes on neurons, myelinated fiber tracts, choroid plexus, glial cells, and blood vessels. Antibody-positive patients were younger than antibody-negative patients but did not differ in the extent of cognitive impairment, epidemiological and clinical factors, or comorbidities. Further research is needed to understand the potential contribution to disease progression and symptomatology, and to determine the antigenic targets of dementia-associated autoantibodies.